A general framework for the manufacturing workstation design optimization: a combined ergonomic and operational approach. (March 2013) - del Rio Vilas, David; Longo, Francesco; Monteil, Nadia Rego
A general framework for the effective design, or re-design, of manufacturing workstations under a combined ergonomic and operational optimization approach is presented. This general framework must be regarded as a method for facilitating and supporting engineers and researchers in the design of manufacturing workstations. The three key elements forming this general framework are presented and discussed. Finally to provide evidence on the relevance of the proposed general framework, two original case studies, developed by the authors in cooperation with two real manufacturing systems (one located in Italy and one in Spain), are presented. This paper will provide useful insights and guidelines to engineers, researchers and practitioners involved in manufacturing workstations design.